Use of the ISNT rule for optic disc evaluation in 40 to 79 year old patients seen in optometric practice - Lundmark, Per O.; Skjöld, Göran B.; Nævdal, Paal A.; Volden, Ole K.; Belgum, Morten (Scandinavian Journal of Optometry and Visual Science, 2022)
The purpose this study was to investigate the association between intraocular pressure (IOP) and the outcome of ISNT rule assessment of the optic disc in healthy patients seen in mainstream optometric practice. Consecutive patients over the age of 40 years and with no known general- or ocular pathology were enrolled from 4 optometric practices in Norway and Sweden during a period of 9 months. The sample was stratified by age group (40-49, 50-59, 60-69 and 70-79 years) and ISNT rule outcome (obeyed or broken). Subjects underwent a full optometric examination including stereoscopic assessment of the optic disc with the use of the ISNT rule, followed by measurements of intraocular pressure (IOP), central corneal thickness (CCT) and vertical size of the optic disc. Odds ratio (OR) was used to assess the association between IOP and the outcome measure. Stratified and multivariable analyses were employed to investigate the effect of age, gender, CCT, refractive error and disc size on the association. IOP was dichotomized at a cut-off corresponding to the 75th percentile (18 mmHg), whereas numeric covariables were categorized at cut-offs corresponding to the 33rd (ONH 1.6 mm, CCT 545 μm) and 66th percentile (ONH 1.8 mm, CCT 571 μm), respectively. A total of 177 patients (F: 57%, age range 40-79 years) were included. IOP was significantly higher in patients with broken ISNT rule (16.6 vs. 15.5 mmHg, p = 0.046), corresponding to a crude OR of 2.0 (CI 0.95-4.24). In stratified and multivariable analyses the association between IOP and outcome of the ISNT rule was strengthened in males (OR 4.8) and in subjects with small discs (OR 2.2), however only the effect modification by gender reached significance. Further research is necessary to understand the possible implications of these findings on the assessment of optic discs with the use of the ISNT rule.